The Specifity of the Local Government Elections in the Opolskie Province in 2018 - Ociepa, Marcin (Political Preferences, 2020)
The objective of this paper is to analyse the political activity of the local community of the Opolskie Province in the local government elections in 2018 and to identify the characteristic features determining its specificity. The attempt to identify the electoral specificity of the region will consist in presenting a characterization of the region in terms of its size and population as well as its administrative and social aspects. An analysis of the elements inseparably connected with the election process, such as geography, voting turnout, the number of electoral registers and candidates, the types of electoral committees, is equally important. And finally, comments on the election results are significant as well. The local government elections of 2018 were held in a specific atmosphere, largely related to the amendment of the election law. Undoubtedly, the most characteristic aspect for the Opolskie Region is its last position among other provinces with regard to size and population, but it should not be forgotten that it is a borderland region inhabited by a high percentage of the German national minority, which actively shapes the image of not only the local communities at every level, but also the entire Opolskie Region as such.